Antibacterial effects of zinc oxide nanoparticles on Escherichia coli K88 - Chao Wang, Lian-Long Liu, Ai-Ting Zhang, Peng Xie, Jian-Jun Lu; Xiao-Ting Zou (African Journal of Pig Farming, 2020)
This study was conducted to evaluate the antibacterial effects of zinc oxide nanoparticles in vitro. Escherichia coli K88 was chosen as an indicator of pathogenic bacteria, because it could cause diarrhea in both children and in early-weaned piglets. In this study, the characterization of the nanoparticles was examined. Antibacterial activities against E. coli K88 were evaluated by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) and observing the effects on the values of the optical density (OD) at 620 nm and the populations. Results indicate that zinc oxide nanoparticles had strong antibacterial activity against E. coli K88. The activity increased as the concentration of the nanoparticles increased. The MIC and MBC were 0.1 and 0.8 µg/ml, respectively. To study the antibacterial mechanisms, atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to observe morphological changes of E. coli K88 treated with 0.8 µg/ml zinc oxide nanoparticles. The results reveal that zinc oxide nanoparticles could damage cell membranes, lead to leakage of cytoplasm and kill the bacterial cells. Our study indicates that zinc oxide nanoparticles could potentially be an antibacterial reagent to treat diseases caused by bacteria.